LAYANAN KELOMPOK UNTUK MENGURANGI PERILAKU SISWA YANG MELANGGAR TATA TERTIB SEKOLAH DI SMP NEGERI 17 BANJARMASIN - Yasan, Raymoel; Farial, Farial; Auliah, Nurul (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2019)
Student behavior that violates school rules is the behavior of students who are not responsible for carrying out their duties as students. The purpose of this study was to determine whether there was a reduction in the behavior of students who violated the school rules using group counseling for students of SMP Negeri 17 Banjarmasin. This study uses quantitative methods. This type of research is pre-experimental designs with Onegroup design, pretest-posttest design.Based on the results of the Wilcoxon test data calculation, the Z table obtained for the sig value 0.27 so Zhitung is -2.207, because this value is absolute so that the negative sign is not taken into account. So that the calculated Z value becomes 2.207, then the calculated Z value is compared with the Z table value with a significance level of 6%, the price of Z table = 0. Then Z count = 2.207>Ztable = 0 then Ha is accepted thus the behavior of the violation of the rules there is a change after being given group counseling services seen from the provisions of Zhitung>Ztable and Ho refused. So it can be concluded that group counseling services can reduce the behavior of students who violate the school rules for students who have a very high category to be high in class IX C students in SMP Negeri 17 Banjarmasin.